2021
DOI: 10.1155/2021/6095963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sinapic Acid Combined with Cisplatin on the Apoptosis and Autophagy of the Hepatoma Cells HepG2 and SMMC-7721

Abstract: Sinapic acid (Sa) is a small-molecule phenolic acid compound predominant in fruits, vegetables, and grains. This study investigated the antitumor effects of cisplatin (DDP) combined with Sa (Sa/DDP) on the hepatic cancer cells (HCC), HepG2 and SMMC-7721. The HepG2 and SMMC-7721 cells were treated with Sa or Sa/DDP, and the cell proliferation and cell cycle were detected using the MTT assay. The cell migration was detected using the transwell and scratch assays, while apoptosis and autophagy were detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The autophagy inducing effect of SA has been reported by Zhao et al (2021) in HepG2 and SMMC-7721 cells. MDC staining for autophagy showed increased number of green granular structures in cytoplasm and nucleus area of both SA along with cisplatin treated HepG2 and SMMC-7721 cells compared to the untreated cells.…”
Section: Effect Of Sa On Autophagymentioning
confidence: 92%
See 4 more Smart Citations
“…The autophagy inducing effect of SA has been reported by Zhao et al (2021) in HepG2 and SMMC-7721 cells. MDC staining for autophagy showed increased number of green granular structures in cytoplasm and nucleus area of both SA along with cisplatin treated HepG2 and SMMC-7721 cells compared to the untreated cells.…”
Section: Effect Of Sa On Autophagymentioning
confidence: 92%
“…The findings of the study showed that SA induced an early G0/G1 phase arrest in Hep-2 cells in a dose-dependent manner. Zhao et al (2021) found that SA induced G2/M phase cell cycle arrest in Hep G2 and SMMC-7721 cell lines. The percentage of apoptotic cells of HepG2 cells and SMMC-7721 cells in G2/M phase treatment increased from 12.79 ± 0.89% in control to 22.60 ± 2.26% and 26.00 ± 1.30% after SA along with cisplatin treatment.…”
Section: Effect Of Sa On Cell Cycle Arrestmentioning
confidence: 95%
See 3 more Smart Citations